MOTIVATIONS FOR ATTENDING UNIVERSITY AND DROPOUT INTENTION IN FIRST-YEAR UNIVERSITY STUDENTS - Ana-Maria Cazan; Roxana Elena Stoica; Camelia Truta; Maria Magdalena Stan; Cătălin Ioan Maican (Bulletin of the Transilvania University of Braşov, 2024)
University dropout is considered a critical research topic today due to its significant implications for individuals, institutions, and society. The main aims of this study were to analyse the differences in learning engagement and dropout intention during the first academic year and to analyse the predictive value of motivations to attend university and pre-entry characteristics on the dropout intention. Results showed that learning engagement and dropout intentions vary during the first year, with the decrease in engagement and relative stability towards the end of the year. Students without clear reasons for attending university are most susceptible to dropping out. Learning engagement appears to be a powerful predictor of a low dropout intention.